Management and outcomes of femoral periprosthetic fractures at the hip: data from the characteristics, outcomes and management of periprosthetic fracture service evaluation (COMPOSE) cohort study - Baker, P; Gwilym, S; Gacaferi, H (British Editorial Society of Bone and Joint Surgery, 2022)
Aims The aim of this study was to describe the management and associated outcomes of patients sustaining a femoral hip periprosthetic fracture (PPF) in the UK population.